Analisis Fiqh Zakat Terhadap Pembayaran Zakat Pertanian di Desa Jatipayak, Kecamatan Modo, Kabupaten Lamongan - Tamimah, Tamimah (Journal of Comprehensive Science, 2025)
Islam in overcoming poverty is not half-hearted, namely with zakat. Agricultural products are assets that must be issued zakat if they have reached nishab. The level that must be released is ten percent if the plant is irrigated with rainwater and five percent if it is irrigated using irrigation equipment. In contrast to what happened in Jatipayak village, the people there knew that agricultural zakat was mandatory by law and the community paid zakat every harvest, but the community did not know how much nishab and the rate that had to be spent in agricultural zakat. In this study, using the nature of the research descriptive analysis, data collection using interviews and documentation. Meanwhile, in analyzing data, three stages are used, namely, data reduction, data presentation, and Conclusion drawing/verification. The results of the study show that the payment of agricultural zakat in Jatipayak village is in accordance with the fiqh of zakat. The zakat that is issued is only for rice plants, because rice, according to the imams of the four madhhabs, must be issued zakat. The public does not know that nishab zakat is agricultural and nishab is not a condition of agricultural zakat according to Imam Hanafi. The zakat amount issued by the people of Jatipayak is not appropriate, because they do not know the amount. The distribution of zakat is appropriate, but there are some who are a little obstructed, because there are those who distribute their zakat to orphans, even though orphans are not included in the mustahik zakat. The time to issue zakat is appropriate, namely when the plants have been harvested and separated from the straw and have become rice and are ready to be cooked. Keywords: Fiqh Zakat, Agricultural Zakat.